2019
DOI: 10.3117/plantroot.13.9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of strontium on the growth, ion balance, and suberin induction in <i>Solanum lycopersicum</i>

Abstract: Or ri ig gi in na al l r re es se ea ar rc ch h a ar rt ti ic cl le e R Re ev vi ie ew w a ar rt ti ic cl le e S Sh ho or rt t r re ep po or rt t Nagata T 2019 Effect of strontium on the growth, ion balance, and suberin induction in Solanum lycopersicum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…This fact raises the following question, under which conditions can we utilise "Sr 2+ as a tracer for Ca 2+ " without experiencing the adverse, toxic effects? In a study on tomato seedling grown in agar medium for two weeks, Sr 2+ toxicity leads to a signi cant reduction in shoot and root biomass at Sr 2+ concertation of 4mM and above (Nagata 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This fact raises the following question, under which conditions can we utilise "Sr 2+ as a tracer for Ca 2+ " without experiencing the adverse, toxic effects? In a study on tomato seedling grown in agar medium for two weeks, Sr 2+ toxicity leads to a signi cant reduction in shoot and root biomass at Sr 2+ concertation of 4mM and above (Nagata 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that plants could accumulate not only Ca but also Sr (Tsukada 2005, Uchida 2007b). Plant species, including Arabidopsis thaliana (A. Thaliana) (Kanter 2010), Glycine max (G. max, soybean) (Sowa 2014, Wojciak-Kosior 2016, Amaranthus caudatus (Chu 2015), and Solanum lycopersicum (Nagata 2019) have been reported to accumulate higher Sr content in the shoots than the roots. Analysis of metal ions and phytoestrogens, such as daidzein and genistin in soybean showed that Sr induced Ca content in the leaves and roots, but decreased the phytoestrogens levels (Hanaka et al 2019).…”
Section: Introductionmentioning
confidence: 99%